Acute Diplopia Following Rhinoplasty: Clearing the Air. Issue 2 (May 2023) - Boustany, Ashley N.; Comer, Carly D.; Gopal, Harsha; Lin, Samuel J.; Slavin, Sumner A.
Diplopia after rhinoplasty is a rare complication that requires immediate medical attention. Workup should include a complete history and physical examination, appropriate imaging, and consultation with ophthalmology. Diagnosis may be challenging due to the wide differential ranging from dry eyes to orbital emphysema to an acute stroke. Patient evaluation should be expedient, though thorough to facilitate time-sensitive therapeutic interventions. Here, we present a case of transient binocular diplopia presenting 2 days after closed septorhinoplasty. The visual symptoms were attributed to either intra-orbital emphysema or a decompensated exophoria. This is the second documented case of orbital emphysema after rhinoplasty presenting with diplopia. It is the only case with a delayed presentation as well as the only case that resolved after positional maneuvers.